2020
DOI: 10.21608/auej.2020.103773
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life Prediction of Un-Notched Round Specimens Based on Cracking Simulation

Abstract: This work presents a cracking damage model to assess fatigue lives of un-notched round specimens in axial stresses due to constant and variable amplitude loading. The model numerically simulates collective behavior of growing short fatigue surface cracks originating from the surface roughness of specimens made of a two-phase alloy. The specimen roughness is assumed resembling micro cracks of different sizes and locations along the minimum specimen circumference. Material grains of different phases, sizes and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Consequently, the sum of the lengths of cracks present on the notch surface at the root a continuously increases with N . Farag et al 52–54 concluded a similar pattern of short fatigue cracks growing from the rough surface of unnotched round specimens made of a two‐phase alloy.…”
Section: Resultsmentioning
confidence: 91%
“…Consequently, the sum of the lengths of cracks present on the notch surface at the root a continuously increases with N . Farag et al 52–54 concluded a similar pattern of short fatigue cracks growing from the rough surface of unnotched round specimens made of a two‐phase alloy.…”
Section: Resultsmentioning
confidence: 91%